Diaquabis(1,10-phenanthroline)magnesium dichromate(VI) 1,10-phenanthroline disolvate - Liu, Hai-Xing (International Union of Crystallography, 2009)
In the title compound, [Mg(C(12)H(8)N(2))(2)(H(2)O)(2)][Cr(2)O(7)]·2C(12)H(8)N(2), the cation and anion are situated on a twofold rotation axis. The Mg(II) ion is coordinated by four N atoms from two 1,10-phenanthroline ligands and two O atoms from coordinated water molecules in a distorted octahedral geometry. Intermolecular O—H⋯N and O—H⋯O hydrogen bonds and π–π interactions between the aromatic rings [shortest centroid–centroid separation = 3.527 (2) Å] link the cations, anions and 1,10-phenanthroline solvent molecules into a hydrogen-bonded cluster.